Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Let's find the missing values in the table step-by-step.
Given the line equation:
[tex]\[ y = -\frac{2}{3}x + 7 \][/tex]
1. Finding [tex]\(y\)[/tex] when [tex]\(x = -6\)[/tex]:
[tex]\[ y = -\frac{2}{3}(-6) + 7\][/tex]
[tex]\[ y = 4 + 7 \][/tex]
[tex]\[ y = 11 \][/tex]
So, the corresponding [tex]\( y \)[/tex] value for [tex]\( x = -6 \)[/tex] is 11.
2. Finding [tex]\(x\)[/tex] when [tex]\( y = 5 \)[/tex]:
We use the equation and solve for [tex]\( x \)[/tex]:
[tex]\[ 5 = -\frac{2}{3}x + 7 \][/tex]
Subtract 7 from both sides:
[tex]\[ 5 - 7 = -\frac{2}{3}x \][/tex]
[tex]\[ -2 = -\frac{2}{3}x \][/tex]
Divide both sides by [tex]\(-\frac{2}{3}\)[/tex]:
[tex]\[ x = \frac{-2}{-\frac{2}{3}} \][/tex]
[tex]\[ x = 3 \][/tex]
So, the corresponding [tex]\( x \)[/tex] value for [tex]\( y = 5 \)[/tex] is 3.
3. Finding [tex]\(y\)[/tex] when [tex]\(x = 15\)[/tex]:
[tex]\[ y = -\frac{2}{3}(15) + 7 \][/tex]
[tex]\[ y = -10 + 7 \][/tex]
[tex]\[ y = -3 \][/tex]
So, the corresponding [tex]\( y \)[/tex] value for [tex]\( x = 15 \)[/tex] is -3.
4. Finding [tex]\(x\)[/tex] when [tex]\( y = 15 \)[/tex]:
We use the equation and solve for [tex]\( x \)[/tex]:
[tex]\[ 15 = -\frac{2}{3}x + 7 \][/tex]
Subtract 7 from both sides:
[tex]\[ 15 - 7 = -\frac{2}{3}x \][/tex]
[tex]\[ 8 = -\frac{2}{3}x \][/tex]
Divide both sides by [tex]\(-\frac{2}{3}\)[/tex]:
[tex]\[ x = \frac{8}{-\frac{2}{3}} \][/tex]
[tex]\[ x = -12 \][/tex]
So, the corresponding [tex]\( x \)[/tex] value for [tex]\( y = 15 \)[/tex] is -12.
Now we fill in the table with these values:
\begin{tabular}{|c|c|}
\hline [tex]$x$[/tex] & [tex]$y$[/tex] \\
\hline -6 & 11 \\
\hline 3 & 5 \\
\hline 15 & -3 \\
\hline -12 & 15 \\
\hline
\end{tabular}
Given the line equation:
[tex]\[ y = -\frac{2}{3}x + 7 \][/tex]
1. Finding [tex]\(y\)[/tex] when [tex]\(x = -6\)[/tex]:
[tex]\[ y = -\frac{2}{3}(-6) + 7\][/tex]
[tex]\[ y = 4 + 7 \][/tex]
[tex]\[ y = 11 \][/tex]
So, the corresponding [tex]\( y \)[/tex] value for [tex]\( x = -6 \)[/tex] is 11.
2. Finding [tex]\(x\)[/tex] when [tex]\( y = 5 \)[/tex]:
We use the equation and solve for [tex]\( x \)[/tex]:
[tex]\[ 5 = -\frac{2}{3}x + 7 \][/tex]
Subtract 7 from both sides:
[tex]\[ 5 - 7 = -\frac{2}{3}x \][/tex]
[tex]\[ -2 = -\frac{2}{3}x \][/tex]
Divide both sides by [tex]\(-\frac{2}{3}\)[/tex]:
[tex]\[ x = \frac{-2}{-\frac{2}{3}} \][/tex]
[tex]\[ x = 3 \][/tex]
So, the corresponding [tex]\( x \)[/tex] value for [tex]\( y = 5 \)[/tex] is 3.
3. Finding [tex]\(y\)[/tex] when [tex]\(x = 15\)[/tex]:
[tex]\[ y = -\frac{2}{3}(15) + 7 \][/tex]
[tex]\[ y = -10 + 7 \][/tex]
[tex]\[ y = -3 \][/tex]
So, the corresponding [tex]\( y \)[/tex] value for [tex]\( x = 15 \)[/tex] is -3.
4. Finding [tex]\(x\)[/tex] when [tex]\( y = 15 \)[/tex]:
We use the equation and solve for [tex]\( x \)[/tex]:
[tex]\[ 15 = -\frac{2}{3}x + 7 \][/tex]
Subtract 7 from both sides:
[tex]\[ 15 - 7 = -\frac{2}{3}x \][/tex]
[tex]\[ 8 = -\frac{2}{3}x \][/tex]
Divide both sides by [tex]\(-\frac{2}{3}\)[/tex]:
[tex]\[ x = \frac{8}{-\frac{2}{3}} \][/tex]
[tex]\[ x = -12 \][/tex]
So, the corresponding [tex]\( x \)[/tex] value for [tex]\( y = 15 \)[/tex] is -12.
Now we fill in the table with these values:
\begin{tabular}{|c|c|}
\hline [tex]$x$[/tex] & [tex]$y$[/tex] \\
\hline -6 & 11 \\
\hline 3 & 5 \\
\hline 15 & -3 \\
\hline -12 & 15 \\
\hline
\end{tabular}
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.